GLOBAL-LOCAL ENVIRONMENT CERTIFICATION AT FIVE STAR HOTELS IN TOURISM AREA OF NUSA DUA, BALI - Suci Murni, Ni Gst Nym; Anom Kumbara, AAN; Sirtha, I Nyoman; Mudana, I Gede (E-Journal of Cultural Studies; Volume 7, Number 2, May 2014)
The research aims to examine the various form of environment certification, ideology behind the practice of green tourism (global award) and Tri Hita Karana (local award), and the implication of environment practice at five star hotel in Nusa Dua tourism area. The data of the reserach was assessed by postmodern critical theory (theory of discourse regarding power/knowledge, hegemony theory, practice theory, and theory of deep/shallow ecology. The method used in this cultural studies is the qualitative one, where the data collection were obtained through direct observation, in-depth interviews, and related documentation. The sample used 6 five star hotels which practise green award, of 14 established five star hotels (some hotel is not in full operation).  The results showed that (1) there are some variation of environment practice in five star hotel, (2) ideology working behind these practices can be seen from global ideology in the form of sustainable development deriving green tourism, and the local ideology, in the form of Tri Hita Karana (THK) used in THK award, (3) implication of global-local invironment practice in tourism area and surrounding.
Keywords: global-local, environment certification, five star hotel, tourism area.